2003
DOI: 10.1002/jbm.a.10501
|View full text |Cite
|
Sign up to set email alerts
|

Biologic significance of surface microroughing in bone incorporation of porous bioactive glass implants

Abstract: A novel chemical etching method was recently developed to create a controlled microrough surface on porous bioactive glass implants. Our earlier in vitro studies showed enhanced attachment of osteoblast-like MG63 cells on a microrough bioactive glass surface. The purpose of our current study was to confirm the in vivo significance of surface microroughening for bone bonding of bioactive glass. Porous bioactive glass cones made of sintered microspheres were surgically implanted in the anterior cortex of rabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…The ability of bioactive glass scaffolds to support cell proliferation and function in vitro and tissue ingrowth in vivo has been shown in numerous studies [90, 106, 139142] [97, 115]. Fu et al [90] showed that 13–93 bioactive glass scaffolds prepared using a polymer foam replication method supported the attachment and proliferation of MC3T3-E1 pre-osteoblastic cells both on the surface and within the interior pores of the scaffold (Figs.…”
Section: In Vitro and In Vivo Response Of Bioactive Glass Scaffoldsmentioning
confidence: 99%
“…The ability of bioactive glass scaffolds to support cell proliferation and function in vitro and tissue ingrowth in vivo has been shown in numerous studies [90, 106, 139142] [97, 115]. Fu et al [90] showed that 13–93 bioactive glass scaffolds prepared using a polymer foam replication method supported the attachment and proliferation of MC3T3-E1 pre-osteoblastic cells both on the surface and within the interior pores of the scaffold (Figs.…”
Section: In Vitro and In Vivo Response Of Bioactive Glass Scaffoldsmentioning
confidence: 99%
“…5 The bioactivity of these sintered bodies has been tested in vivo. 6 The increased workability often means also changes in the bioactivity of the glass leading to only medium or low bioactivity. 7 Although the understanding of the influence of different components on both the bioactivity and the working properties has increased, still the most clinically used bioactive glasses are plates, granules and powdered glass, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that different cell types react to patterned surfaces: Roughened biomaterial surfaces in the micrometer range can enhance cell adhesion in vitro [37,38] and bone-to-implant contact in vivo [3]. Itälä et al have shown that microroughening of porous bioactive glass surfaces enhance the biological activity of certain bioactive glass compositions [22]. In this study first live/dead experiments on structured bioactive glasses have shown that almost all cells appear green, displaying alive cells.…”
Section: Discussionmentioning
confidence: 62%
“…Following in vivo experiments even showed a higher amount of incorporated new bone in comparison to smooth implants [22]. Porous structures were realized by lithography-based additive manufacturing as well, creating crystallized bioglass samples [23].…”
Section: Introductionmentioning
confidence: 99%